Physiological Changes in Subjects Exposed to Accidental Hypothermia: An Update - Bjertnæs, Lars J.; Næsheim, Torvind O.; Reierth, Eirik; Suborov, Evgeny V.; Kirov, Mikhail Y.; Lebedinskii, Konstantin M.; Tveita, Torkjel (Frontiers in Medicine, 2022)
Background Accidental hypothermia (AH) is an unintended decrease in body core tempera-ture (BCT) to below 35 °C. We present an update on physiological/pathophysiological changes associated with AH and rewarming from hypothermic cardiac arrest (HCA). Temperature regulation and Metabolism Triggered by falling skin temperature, Thyrotro-pin-Releasing Hormone (TRH) from hypothalamus induces release of Thyroid-Stimulating Hormone (TSH) and Prolactin from pituitary gland anterior lobe that stimulate thyroid genera-tion of triiodothyronine and thyroxine (T4). The latter act together with noradrenaline to in-duce heat production by binding to adrenergic 3-receptors in fat cells. Exposed to cold, nor-adrenaline prompts degradation of triglycerides from brown adipose tissue (BAT) into free fatty acids that uncouple metabolism to heat production, rather than generating adenosine triphosphate. If BAT is lacking, AH occurs more readily. Cardiac output (CO) Assuming a 7 % drop in metabolism per ‎°C, a BCT decrease of 10 o C can reduce metabolism by 70 % paralleled by a corresponding decline in CO. Consequently, it is possible to maintain adequate oxygen delivery provided correctly performed cardiopulmo-nary resuscitation (CPR), which might result in approximately 30 % of CO generated at nor-mal BCT. Liver and Coagulation AH promotes coagulation disturbances following trauma and acidosis by reducing coagulation and platelet functions. Mean prothrombin and partial thromboplastin times might increase by 40% - 60 % in moderate hypothermia. Rewarming might release tissue factor from damaged tissues, that triggers disseminated intravascular coagulation. Hypother-mia might inhibit platelet aggregation and coagulation. Kidneys Renal blood flow decreases due to vasoconstriction of afferent arterioles, electrolyte and fluid disturbances and increasing blood viscosity. Severely deranged renal function occurs particularly in the presence of rhabdomyolysis induced by severe AH combined with trauma. Conclusions Metabolism drops 7 % per ‎°C fall in BCT, reducing CO correspondingly. There-fore, it is possible to maintain adequate oxygen delivery after 10 ‎°C drop in BCT provided correctly performed CPR. Hypothermia may facilitate rhabdomyolysis in traumatized patients. Victims suspected of HCA should be rewarmed before being pronounced dead. Rewarming avalanche victims of HCA with serum potassium > 12 mmol/L and a burial time > 30 min with no air pocket, most probably be futile.